Polemics and discursive ethos from a linguistic-discursive perspective - Paré Glück, Eduardo (2021)
Polemics can be found in many debates and discussions on the Internet, especially when the topic in question involves politics. To understand how a politico-social text involving a polemics and a prominent topic is developed is necessary nowadays. Thus, this study aims to verify the nature and the discursive ethos of the speaker of an opinion article published on Folha de São Paulo. Maingueneau (2002; 2008), to address the discursive ethos, and Amossy (2008; 2017a), in order to verify the marks of the discursive polemics, are the basic references. The results show a polemics text that carries a discursive ethos that is enunciatively revealed by means of irony, negation and the handling of the other. It is concluded that, although Folha de São Paulo is characterized as a non-partisan newspaper, it is possible to reveal the enunciator's discursive ethos, as well as the controversial nature, from linguistic-discursive marks contained in the text.